Football Player Decision Support System Baghdad-City as a Case Study - Salman, Ban; M. Alhakkak, Nada; Musa Jaber, Mustafa (International Journal of Engineering and Technology, 2018)
Decision support system (DSS) is an area of information systems (IS) discipline which focuses on supporting decision-making. DSS includes personal decision support systems, executive information systems, online analytical processing systems, data warehousing, business intelligence, and group support systems. This paper introduced the implementation of a DSS related to football players with a case study.Â